SPATIAL VISUAL INTELLIGENCE AND LEARNING INDEPENDENCE IN INFORMAL LEARNING RESULTS AT HOME DURING THE PANDEMI COVID-19 - Muhammad Sujatmiko (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Spatial visual intelligence has a significant influence on the online learning process because of the independence of students in the informal learning process. Furthermore, this study aims to determine the relationship of spatial visual intelligence and learning independence to student learning outcomes in online learning activities during the COVID-19 pandemic, especially in the DPTM (Basic Mechanical Engineering Design) subject in class X TPM SMK Negeri 6 Malang in the 2020 academic year. / 2021. The design of this study is a correlation with a quantitative approach. The subjects of this study were 82 students of class X Mechanical Engineering at SMK Negeri 6 Malang. Data collection techniques are tests, questionnaires, and documentation. The data analysis used linear and multiple regression statistics. The results showed that visual spatial intelligence and students' learning independence were high in the basic subjects of Mechanical Engineering Planning. Each variable has a relationship and influence on student learning outcomes. This is indicated by the value of student learning outcomes with high criteria. So, it can be concluded that each variable simultaneously has a positive effect on learning outcomes.